An historical survey of the Bethelsdorp station of the London Missionary Society, from its inception, and until the death of Doctor van der Kemp, in 1811 - Briggs, D Roy (Rhodes University, Faculty of Divinity, Department of Divinity, 1952)
In South Africa the small town or hamlet, nestling - as is so often the case - at the foot of a mountain, frequently proclaims its identity to the traveller by inscribing its name in great, white-washed letters of stone upon the side of the hill. If this were the case with Bethelsdorp, the temptation would be to write on those bare, rocky hills, that form the back-drop for the drama a century and a half have seen on its stage, the one word, "Ichabod." For the glory has departed. And some would even question whether any of its days had been glorious. Around this small outpost of Christendom have centred, from its earliest beginnings, both praise and contumely. It is the purpose of this investigation to attempt to judge between these opinions, in an attempt to arrive at the truth, by a survey of the years Bethelsdorp enjoyed under the direction of Johannes Theodorus van der Kemp. He has had many critics, many protagonists: perhaps of no other man in the short history of this land has there been such diversity of opinion. Before the judgments of historians and biographers can be assessed, however, the facts of his work must be appreciated, and the effort towards understanding must be preceded by a brief description of the circumstances antecedent to the foundation of that station, which marked the summt of his life and work.
Keywords: London Missionary Society -- History; Bethelsdorp (South Africa) -- History